Respon Belajar Penerapan Model Contextual Teaching And Learning Dibandingkan Dengan Think Pair Share Pada Siswa - Atan Pramana (IAI Darussalam, 2017)
The purpose of this study to determine the learning response due to the application of Contextual Teaching And Learning model compared with Think Pair Share on PC PC learning outcomes of class X TKJ. This research is a quasi experimental research (quasi experiment). The sample is determined by class X TKJ 3 with treatment of Contextual Teaching And Learning model and class X TKJ 1 with treatment of Think Pair Share learning model. Instrument of measurement of learning result include assessment of test, affective rubric, and psychomotor rubric which previously performed instrument validation test. Data analysis technique using SPSS-assisted t-test 20. Based on the results of research and data analysis conducted There is a contribution of learning responses in the implementation of Contextual Teaching and Learning model of 71.5%, while the contribution of learning responses of the application of Think Pair Share learning model is 67.8 %. Of the percentage is known that the student's learning response to the application of Contextual Teaching And Learning model is higher than the student's learning response to the application of Think Pair Share